Terapia Assistida por Animais: sua eficácia no desempenho cognitivo de idosos institucionalizados - Franceschini, Belinda Talarico (2017)
Ageing is a process which brings a number of biopsychosocial changes and, now a days, this process is a demographic reality due to population ageing. In view of this it’s seen the increase of the prevalence of cognitive changes and institutionalization in elderly people, both factors that are harmful for their health. This points out the necessity of a quality of life improvement strategy for elderly people, and the Animal-Assisted Therapy (AAT) is a strategy that has contributed to this. Therefore, the objective of this study is to evaluate the effectiveness of AAT, specifically Cinoterapia, in cognitive development and depressive symptoms of elderly people. This is an experimental study, therefore, it aims to explore the connection between the variables, and, specifically in this case, the relation between AAT and cognitive development of institutionalized elders. This study is the pre-test-post-test type, aiming to measure the individual level of change after the AAT intervention. The instruments used were Mini-Mental State Examination, verbal fluency test animals category and the Geriatric Depression Scale (15 points version). The location used for this study was a Long-Term Care Institution in São Carlos where thirteen residents with cognitive decline pointed by the instruments used agreed to participate. The participants were separated in two groups, the Experimental Group (subjected to intervention) and Control Group (not subjected to intervention).Based on the results of the instruments e and the behavior of the participants, the data collected before and after the test show us that AAT is an effective strategy for the cognitive performance and quality of life of institutionalized elders.